HUBUNGAN SELF-REGULATED LEARNING DENGAN HASIL BELAJAR PENDIDIKAN JASMANI ADAPTIF SISWA TUNADAKSA - Widya Martha, Bayu (Jurnal Pendidikan Khusus, 2016)
HUBUNGAN SELF-REGULATED LEARNING DENGAN HASIL BELAJAR PENDIDIKAN JASMANI ADAPTIF SISWA TUNADAKSA Bayu Widya Martha dan Endang Pudjiastuti Sartinah Jurusan Pendidikan Luar Biasa, Fakultas Ilmu Pendidikan, Universitas Negeri Surabaya, bayuwidya@ymail.com Abstract The purpose of this study was to determine the relationship of self-regulated learning with learning outcomes of adapted physical education of students with physical disabilities of YPAC Surabaya. Students with physical disabilities as students with motor constraints require services to optimize their motor ability. In formal education, adapted physical education is one that stimulates motor of students with physical disabilities. As a learning process, there are various factors that affect the outcome. One of the factors that affect the learning outcomes is self-regulated learning. This study uses a quantitative approach to the type of correlational research. The subjects of the study consisted of students with physical disabilities without barriers in thinking in SDLB-D, SMPLB, and SMALB YPAC Surabaya totaling 17 students. The technique of collecting data using interviews, observations, and tests. Processing data using Spearman Rank and analysis of data using Linear Regression Analysis. The results showed r = 0.120 and determination coefficient of self-regulated learning towards learning outcomes of adapted physical education at 0.0144 or 1.44%. Results of linear regression analysis showed the equation Y = 48 + 0,2X. Conclusion from this research is that self-regulated learning with learning outcomes of adapted physical education of students with physical disabilities of YPAC Surabaya has a very low level of relationship. Self-regulated learning determine learning outcomes of adapted physical education is only 1.44%. Keywords: self-regulated learning, adapted physical education